Mining Raton History - 20160731 frey50 (McKinleyville, California Coda Publications, 2012)
Evelyn Shuler and former Mayor Jams Mahler begin this fine collection of first-person reports about Raton's mines and living history. Here are nearly 400 pages of important events, including the Centennial honoring Raton's 1891 founding. Followed by first-person tales of mines and miners, up until 1980 when the folowing taped interviews were recorded for Raton.
Final result of Oral History report conceived and executed by Librarian Betty Lloyd in 1981.
Keywords: Mines -- Raton, New Mexico -- Mining; Miners -- Raton, New Mexico -- Oral History; Living History